2020
DOI: 10.1109/lwc.2020.2988999
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Signal-and-Interference Alignment for Two-Cell Over-the-Air Computation

Abstract: The next-generation wireless networks are envisioned to support large-scale sensing and distributed machine learning, thereby enabling new intelligent mobile applications. One common network operation will be the aggregation of distributed data (such as sensor observations or AI-model updates) for functional computation (e.g., averaging) so as to support large-scale sensing and distributed machine learning. An efficient solution for data aggregation, called over-the-air computation (AirComp), embeds functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Cooperative interference management for AirComp networks remains a largely uncharted area. Recently, an initial study in this area was reported in [26], where a scheme called simultaneous signal-and-interference alignment is proposed to maximize the number of interference-free aggregated data streams in a two-cell AirComp network. In this work, we study the same theme of multi-cell cooperation but from a different perspective, namely power control.…”
Section: B Cooperative Interference Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…Cooperative interference management for AirComp networks remains a largely uncharted area. Recently, an initial study in this area was reported in [26], where a scheme called simultaneous signal-and-interference alignment is proposed to maximize the number of interference-free aggregated data streams in a two-cell AirComp network. In this work, we study the same theme of multi-cell cooperation but from a different perspective, namely power control.…”
Section: B Cooperative Interference Managementmentioning
confidence: 99%
“…We denote {Q opt2 k } k∈K ℓ and ν opt2 ℓ as the optimal solution to problem (P2.2.ℓ). Let λ ℓ,j ≥ 0 denote the dual variable associated with the j-th IT constraint in (26) for problem (P2.2.ℓ). Then the partial Lagrangian of problem (P2.2.ℓ) is given by…”
Section: B Distributed Power Control Under It Constraintsmentioning
confidence: 99%
See 3 more Smart Citations